HBR working moms collection - Dowling, Daisy; Harvard Business Review Press (Boston, Massachusetts : Harvard Business Review Press, 2022)
Manage the competing demands of working motherhood. As a working mother, you often draw the short straw. You carry most of the burden of caregiving and household chores, and your career can suffer because of it. Bosses and coworkers assume that since you're focused on your family, you don't prioritize work. But when you choose your job over quality time with your kids, it feels like you're letting down the people you love most. The HBR Working Moms Collection can help you alleviate this tension. Drawing on the wisdom of world-class experts and parents alike, it will help you strike the right balance between family and work so you can prioritize what matters most and feel fulfilled in all areas of your life. The six books in this set-- Advice for Working Moms, Getting It All Done, Managing Your Career, Taking Care of Yourself, Communicate Better with Everyone, and Two-Career Families--will teach you how to transition back to work effectively, eliminate working-mom guilt, balance being a caregiver with being an employee, prioritize time to address your personal needs, communicate successfully with your employer and with your family, and navigate being part of a two-career family. There's no one simple answer or foolproof tip to make working motherhood easy, but the strategies in this collection can help set you on a path toward finding success, both in your career and as a mom. The HBR Working Parents Series with Daisy Dowling, Series Editor, supports readers as you anticipate challenges, learn how to advocate for yourself more effectively, juggle your impossible schedule, and find fulfillment at home and at work. Whether you're up with a newborn or planning the future with your teen, you'll find the practical tips, strategies, and research you need to make working parenthood work for you.
Includes bibliographical references and index.
Print version record.
Added to collection customer.56279.3
Keywords: Working mothers; Working mothers -- Time management; Work and family; Work and family; Working mothers; Working mothers -- Time management